Low elongation ptfc belt material and process for making same
Patent Information
- Application Number
- CN202510187142.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-02-20
AI Technical Summary
Existing PTFE composite tape materials have high elongation and require further improvement to enhance their wear resistance.
By adjusting the raw material composition and preparation process, low-elongation PTFE composite tape material is prepared, including the use of polytetrafluoroethylene, functional powder, modified fiber, nano titanium dioxide, paraffin oil and antioxidant, and the low-elongation PTFE composite tape material is obtained by mixing, extruding into strips, calendering into thin sheets and heat treatment.
It achieves low elongation at break and excellent wear resistance, improving the quality and grade of the material, making it suitable for a wide range of applications.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite tape technology, specifically to low-elongation PTFE composite tape materials and their preparation process. Background Technology
[0002] Polytetrafluoroethylene (PTFE) is a high-molecular polymer synthesized from tetrafluoroethylene monomers. It exhibits excellent heat and cold resistance. This material is resistant to acids, alkalis, and various organic solvents, and is virtually insoluble in all solvents. Furthermore, PTFE is heat-resistant, making it suitable for lubrication and an ideal coating for easy-to-clean water pipe interiors.
[0003] The patent application with application number "CN201911328756.8" entitled "PTFE Composite Tape for Aerospace Cables and Its Preparation Method" states that "in the PTFE composite tape of the present invention, the mass of PTFE accounts for 97%-99% of the total mass of the PTFE composite tape, the mass of titanium dioxide accounts for 1%-3% of the mass of PTFE, and the mass of coupling agent accounts for 0.5%-2.5% of the mass of titanium dioxide. The method for preparing the PTFE composite tape of the present invention includes a surface modification step of titanium dioxide, a PTFE powder preparation step, and a PTFE composite tape preparation step. The PTFE composite tape of the present invention has uniform thickness, high UV absorption, excellent thermal stability before 500℃, and a tensile strength of 12.17MPa, an elongation of 122%, and an insulation dielectric strength greater than 95kV / mm, meeting the performance requirements of US military standard SAE AS22795 for high-temperature resistant PTFE composite tapes for aerospace applications."
[0004] While the PTFE composite tapes manufactured in the aforementioned patent documents possess advantages such as thermal stability, their high elongation necessitates further improvement. Therefore, this invention provides a low-elongation PTFE composite tape material and its preparation process to address the aforementioned technical problems! Summary of the Invention
[0005] The purpose of this invention is to provide a low-elongation PTFE composite tape material and its preparation process. The prepared low-elongation PTFE composite tape material not only has a low elongation at break, but also has excellent wear resistance, effectively ensuring its quality and performance.
[0006] To achieve the above objectives, the present invention provides the following technical solution: The first aspect of the present invention provides a low-elongation PTFE composite tape material, which is composed of the following raw materials in parts by weight: 20-30 parts polytetrafluoroethylene, 3-6 parts functional powder, 3-5 parts modified fiber, 2-4 parts nano titanium dioxide, 3-5 parts paraffin oil and 2-5 parts antioxidant.
[0007] The present invention is further configured such that the preparation process of the functional powder is as follows: An appropriate amount of anhydrous ethanol, toluene, and hexadecyltrimethoxysilane were placed in a stirring device at a mass ratio of 1:0.6-0.8:0.12-0.22 and mixed for 20-30 minutes at 120-220 r / min. The pH value was then adjusted to 8.2-8.8 with sodium hydroxide solution to obtain the pre-mixed solution. Then, add 0.23–0.43% of the pre-mixed liquid as base material, and treat it at 8000–10000 r / min for 20–30 min. Then, continue to treat it at 60–64℃ and 120–220 r / min for 300–320 min. After filtration, wash it 2–4 times with anhydrous ethanol and deionized water, respectively. Dry the washing product at 50–60℃ for 10–12 h to obtain the functional powder.
[0008] A further provision of the present invention is that the preparation process of the base material is as follows: A suitable amount of titanium source material was placed in a suitable amount of deionized water at a mass ratio of 0.12 to 0.22:1 and treated at 120 to 220 r / min for 20 to 30 min. Silica was added and the pH value was adjusted to 7.0 to 7.4 with sodium hydroxide solution. The mixture was then treated at 55 to 65℃ for 100 to 120 min. After cooling to room temperature, the mixture was filtered. The resulting filter cake was washed 2 to 4 times with deionized water and dried at 50 to 60℃ for 4 to 5 h to obtain the dried product. The dried product was placed in an appropriate amount of deionized water and ultrasonically treated for 20-30 minutes at a solid-liquid ratio of 0.02-0.05 g / mL. Then, an appropriate amount of glacial acetic acid was added to adjust the pH value to 2.1-2.5. The product was then dried at 50-60℃ for 4-5 hours and calcined at 510-520℃ for 120-140 minutes to obtain the base material.
[0009] A further feature of this invention is that the titanium source material is selected from either titanium nitrate or titanium sulfate.
[0010] A further feature of this invention is that the amount of silicon dioxide added is 20-26% of the mass of the titanium source material.
[0011] A further provision of the present invention is that the preparation process of the modified fiber is as follows: The nano-hollow glass microspheres were placed in a compound solution at a solid-liquid ratio of 0.02–0.12 g / mL for 24–26 h, filtered, and then treated at 120–130 °C for 100–120 min to obtain pretreated nano-hollow glass microspheres. Basalt fibers were ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.02–0.08 g / mL for 20–30 min. Then, 0.13–0.33% citric acid was added to the basalt fibers, and the mixture was treated at 120–140 r / min for 25–35 min. The temperature was then raised to 60–70 °C and kept at 140–150 min. The mixture was then treated at 5–10 °C and 120–140 r / min for 30–40 min. After filtration, the mixture was washed 2–4 times with deionized water and then dried at 50–60 °C for 10–12 h to obtain pretreated basalt fibers. Pretreated basalt fibers were ultrasonically dispersed in N,N-dimethylformamide at a solid-liquid ratio of 0.02–0.06 g / mL for 4–10 h. 1.4–6.4% of pretreated hollow glass nanospheres were added to the mixture, and the mixture was treated at 85–135 °C for 3–6 h. After filtration, the mixture was washed 2–4 times with deionized water and then dried at 50–60 °C for 10–12 h to obtain modified fibers.
[0012] The present invention is further configured such that the compound solution is prepared by mixing N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, ethanol and distilled water in a mass ratio of 1:8.8-9.2:1.2-1.4.
[0013] The present invention is further configured such that the antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.
[0014] A second aspect of the present invention also provides a process for preparing the above-mentioned low-elongation PTFE composite tape material, comprising the following steps: Step 1: Accurately weigh polytetrafluoroethylene, functional powder, modified fiber, nano titanium dioxide, paraffin oil and antioxidant, and put them into the mixing equipment for mixing and stirring. Step 2: After the mixture is evenly mixed, the mixture is extruded into strips using a pusher at 60-150℃, and then rolled into thin sheets using a twin-roll calender at 92-100℃. The resulting thin sheets are then rolled at room temperature using a twin-roll calender to obtain a semi-finished PTFE composite belt. Step 3: Heat the obtained PTFE composite tape semi-finished product at 310-330℃ for 12-22 seconds to obtain low elongation PTFE composite tape material.
[0015] Compared with the prior art, the beneficial effects of the present invention are: This invention involves mixing polytetrafluoroethylene (PTFE), functional powders, modified fibers, nano-titanium dioxide, paraffin oil, and antioxidants in a mixing device. After homogeneous mixing, the mixture is extruded into strips using a pusher, then rolled into thin sheets using a two-roll calender. The resulting sheets are then calendered at room temperature using the same two-roll calender to obtain a PTFE composite tape semi-finished product. Finally, the semi-finished PTFE composite tape is heated to obtain a low-elongation PTFE composite tape material. The low-elongation PTFE composite tape material prepared by this invention not only has a low elongation at break but also excellent wear resistance, effectively ensuring its quality. The low-elongation PTFE composite tape material and its preparation process provided by this invention have a broader market prospect and are more suitable for widespread application. Detailed Implementation
[0016] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0017] Example 1: This example provides a low elongation PTFE composite tape material, which is composed of the following raw materials in parts by weight: 20 parts polytetrafluoroethylene, 3 parts functional powder, 3 parts modified fiber, 2 parts nano titanium dioxide, 3 parts paraffin oil and 2 parts antioxidant.
[0018] The preparation process of functional powders is as follows: An appropriate amount of anhydrous ethanol, toluene, and hexadecyltrimethoxysilane were placed in a stirring device at a mass ratio of 1:0.6:0.12 and mixed at 120 r / min for 20 min. The pH value was then adjusted to 8.2 with sodium hydroxide solution to obtain the pre-mixed solution. Then, 0.23% of the pre-mixed liquid base material was added to it, and it was treated at 8000 r / min for 20 min, and then treated at 60℃ and 120 r / min for another 300 min. After filtration, it was washed twice with anhydrous ethanol and deionized water, respectively. The washing product was dried at 50℃ for 10 h to obtain functional powder.
[0019] Furthermore, the preparation process of the base material is as follows: An appropriate amount of titanium source material was placed in an appropriate amount of deionized water at a mass ratio of 0.12:1 and treated at 120 r / min for 20 min. Silica was added and the pH value was adjusted to 7.0 with sodium hydroxide solution. The mixture was then treated at 55℃ for 100 min. After cooling to room temperature, the mixture was filtered. The resulting filter cake was washed twice with deionized water and dried at 50℃ for 4 h to obtain the dried product. The dried product was placed in an appropriate amount of deionized water and sonicated for 20 min at a solid-liquid ratio of 0.02 g / mL. Then, an appropriate amount of glacial acetic acid was added to adjust the pH value to 2.1. The product was then dried at 50℃ for 4 h and calcined at 510℃ for 120 min to obtain the base material.
[0020] In addition, titanium nitrate was selected as the titanium source material.
[0021] The amount of silica added is 20% of the mass of the titanium source material.
[0022] The preparation process of the modified fiber is as follows: The nano-hollow glass microspheres were placed in a compound solution at a solid-liquid ratio of 0.02 g / mL and treated for 24 h. After filtration, they were treated at 120 °C for 100 min to obtain pretreated nano-hollow glass microspheres. Basalt fibers were ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.02 g / mL for 20 min. Then, 0.13% citric acid was added to the basalt fibers, and the mixture was treated at 120 r / min for 25 min. The temperature was then raised to 60℃ and kept at 140 min for 140 min. Finally, the mixture was treated at 5℃ and 120 r / min for 30 min. After filtration, the basalt fibers were washed twice with deionized water and then dried at 50℃ for 10 h to obtain the pretreated basalt fibers. Pretreated basalt fibers were ultrasonically dispersed in N,N-dimethylformamide at a solid-liquid ratio of 0.02 g / mL for 4 h. 1.4% of pretreated hollow glass nanospheres were added to the mixture. The mixture was then treated at 85 °C for 3 h. After filtration, the fibers were washed twice with deionized water and then dried at 50 °C for 10 h to obtain the modified fibers.
[0023] Furthermore, the compound solution is prepared by mixing N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, ethanol and distilled water in a mass ratio of 1:8.8:1.2.
[0024] Antioxidant 1010 was selected.
[0025] Furthermore, this embodiment also provides a preparation process for the above-mentioned low-elongation PTFE composite tape material, including the following steps: Step 1: Accurately weigh polytetrafluoroethylene, functional powder, modified fiber, nano titanium dioxide, paraffin oil and antioxidant, and put them into the mixing equipment for mixing and stirring. Step 2: After the mixture is evenly mixed, the mixture is extruded into strips using a pusher at 60°C, and then rolled into thin sheets using a twin-roll calender at 92°C. The resulting thin sheets are then rolled at room temperature using a twin-roll calender to obtain a semi-finished PTFE composite belt. Step 3: Heat the obtained PTFE composite tape semi-finished product at 310℃ for 12s to obtain low elongation PTFE composite tape material.
[0026] Example 2: The preparation process of the low-elongation PTFE composite tape material provided in this example is basically the same as that in Example 1, except that the specific raw material composition and preparation process of the low-elongation PTFE composite tape material in this example are different. The specific raw material composition and preparation process of the low-elongation PTFE composite tape material in this example are as follows: This embodiment provides a low-elongation PTFE composite tape material, which is composed of the following raw materials in parts by weight: 25 parts polytetrafluoroethylene, 4 parts functional powder, 4 parts modified fiber, 3 parts nano titanium dioxide, 4 parts paraffin oil and 4 parts antioxidant.
[0027] The preparation process of functional powders is as follows: An appropriate amount of anhydrous ethanol, toluene, and hexadecyltrimethoxysilane were placed in a stirring device at a mass ratio of 1:0.7:0.17 and mixed at 170 r / min for 25 min. The pH value was then adjusted to 8.4 with sodium hydroxide solution to obtain the pre-mixed solution. Then, 0.33% of the pre-mixed liquid base material was added to it, and it was treated at 9000 r / min for 25 min, and then treated at 62℃ and 170 r / min for 310 min. After filtration, it was washed three times with anhydrous ethanol and deionized water, respectively. The washing product was dried at 55℃ for 11 h to obtain functional powder.
[0028] Furthermore, the preparation process of the base material is as follows: An appropriate amount of titanium source material was placed in an appropriate amount of deionized water at a mass ratio of 0.17:1 and treated at 170 r / min for 25 min. Silica was added and the pH value was adjusted to 7.2 with sodium hydroxide solution. The mixture was then treated at 60℃ for 110 min. After cooling to room temperature, the mixture was filtered. The resulting filter cake was washed three times with deionized water and dried at 55℃ for 5 h to obtain the dried product. The dried product was placed in an appropriate amount of deionized water and sonicated for 25 min at a solid-liquid ratio of 0.03 g / mL. Then, an appropriate amount of glacial acetic acid was added to adjust the pH value to 2.4. The product was then dried at 55℃ for 5 h and calcined at 515℃ for 130 min to obtain the base material.
[0029] In addition, titanium sulfate was selected as the titanium source material.
[0030] The amount of silica added is 23% of the mass of the titanium source material.
[0031] The preparation process of the modified fiber is as follows: The nano-hollow glass microspheres were placed in a compound solution at a solid-liquid ratio of 0.07 g / mL for 25 h, filtered, and then treated at 125 °C for 110 min to obtain pretreated nano-hollow glass microspheres. Basalt fibers were ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.05 g / mL for 25 min. Then, 0.23% citric acid was added to the basalt fibers, and the mixture was treated at 130 r / min for 30 min. The temperature was then raised to 65℃ and kept at 145 min for 145 min. Finally, the mixture was treated at 7℃ and 130 r / min for 35 min. After filtration, the basalt fibers were washed three times with deionized water and then dried at 55℃ for 11 h to obtain the pretreated basalt fibers. Pretreated basalt fibers were ultrasonically dispersed in N,N-dimethylformamide at a solid-liquid ratio of 0.04 g / mL for 6 h. 3.4% of pretreated hollow glass nanospheres were added to the mixture, and the mixture was treated at 115 °C for 5 h. After filtration, the mixture was washed three times with deionized water and then dried at 55 °C for 11 h to obtain modified fibers.
[0032] Furthermore, the compound solution is prepared by mixing N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, ethanol and distilled water in a mass ratio of 1:9:1.3.
[0033] Antioxidant 1010 was selected.
[0034] Furthermore, this embodiment also provides a preparation process for the above-mentioned low-elongation PTFE composite tape material, including the following steps: Step 1: Accurately weigh polytetrafluoroethylene, functional powder, modified fiber, nano titanium dioxide, paraffin oil and antioxidant, and put them into the mixing equipment for mixing and stirring. Step 2: After the mixture is evenly mixed, the mixture is extruded into strips using a pusher at 90°C, and then rolled into thin sheets using a twin-roll calender at 97°C. The resulting thin sheets are then rolled at room temperature using a twin-roll calender to obtain a semi-finished PTFE composite belt. Step 3: Heat the obtained PTFE composite tape semi-finished product at 320℃ for 17s to obtain low elongation PTFE composite tape material.
[0035] Example 3: The preparation process of the low-elongation PTFE composite tape material provided in this example is basically the same as that in Example 1, except that the specific raw material composition and preparation process of the low-elongation PTFE composite tape material in this example are different. The specific raw material composition and preparation process of the low-elongation PTFE composite tape material in this example are as follows: This embodiment provides a low-elongation PTFE composite tape material, which is composed of the following raw materials in parts by weight: 30 parts polytetrafluoroethylene, 6 parts functional powder, 5 parts modified fiber, 4 parts nano titanium dioxide, 5 parts paraffin oil and 5 parts antioxidant.
[0036] The preparation process of functional powders is as follows: An appropriate amount of anhydrous ethanol, toluene, and hexadecyltrimethoxysilane were placed in a stirring device at a mass ratio of 1:0.8:0.22 and mixed at 220 r / min for 30 min. The pH value was then adjusted to 8.8 with sodium hydroxide solution to obtain the pre-mixed solution. Then, 0.23–0.43% of the pre-mixed liquid base material was added, and the mixture was treated at 10,000 r / min for 30 min, and then further treated at 64 °C and 220 r / min for 320 min. After filtration, the mixture was washed four times with anhydrous ethanol and deionized water, and the washing product was dried at 60 °C for 12 h to obtain the functional powder.
[0037] Furthermore, the preparation process of the base material is as follows: An appropriate amount of titanium source material was placed in an appropriate amount of deionized water at a mass ratio of 0.22:1 and treated at 220 r / min for 30 min. Silica was added and the pH value was adjusted to 7.4 with sodium hydroxide solution. The mixture was then treated at 65℃ for 120 min. After cooling to room temperature, the mixture was filtered. The resulting filter cake was washed four times with deionized water and dried at 60℃ for 5 h to obtain the dried product. The dried product was placed in an appropriate amount of deionized water and sonicated for 30 min at a solid-liquid ratio of 0.05 g / mL. Then, an appropriate amount of glacial acetic acid was added to adjust the pH value to 2.5. The product was then dried at 60℃ for 5 h and calcined at 520℃ for 140 min to obtain the base material.
[0038] In addition, titanium nitrate was selected as the titanium source material.
[0039] The amount of silica added is 26% of the mass of the titanium source material.
[0040] The preparation process of the modified fiber is as follows: The nano-hollow glass microspheres were placed in a compound solution at a solid-liquid ratio of 0.12 g / mL for 26 h, filtered, and then treated at 130 °C for 120 min to obtain pretreated nano-hollow glass microspheres. Basalt fibers were ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.08 g / mL for 30 min. Then, 0.33% citric acid was added to the basalt fibers, and the mixture was treated at 140 r / min for 35 min. The temperature was then raised to 70℃ and kept at 150 min for 150 min. Finally, the mixture was treated at 10℃ and 140 r / min for 40 min. After filtration, the basalt fibers were washed four times with deionized water and then dried at 60℃ for 12 h to obtain the pretreated basalt fibers. Pretreated basalt fibers were ultrasonically dispersed in N,N-dimethylformamide at a solid-liquid ratio of 0.06 g / mL for 10 h. Pretreated basalt fibers and 6.4% pretreated hollow glass nanospheres were added to the mixture. The mixture was then treated at 135 °C for 6 h. After filtration, the fibers were washed four times with deionized water and dried at 60 °C for 12 h to obtain the modified fibers.
[0041] Furthermore, the compound solution is prepared by mixing N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, ethanol and distilled water in a mass ratio of 1:9.2:1.4.
[0042] Antioxidant 1010 was selected.
[0043] Furthermore, this embodiment also provides a preparation process for the above-mentioned low-elongation PTFE composite tape material, including the following steps: Step 1: Accurately weigh polytetrafluoroethylene, functional powder, modified fiber, nano titanium dioxide, paraffin oil and antioxidant, and put them into the mixing equipment for mixing and stirring. Step 2: After the mixture is evenly mixed, the mixture is extruded into strips using a press at 150°C, and then rolled into thin sheets using a twin-roll calender at 100°C. The resulting thin sheets are then rolled at room temperature using a twin-roll calender to obtain a semi-finished PTFE composite belt. Step 3: Heat the obtained PTFE composite tape semi-finished product at 330℃ for 22s to obtain low elongation PTFE composite tape material.
[0044] Comparative Example 1: The difference from Example 1 is that this example does not contain functional powder.
[0045] Comparative Example 2: The difference from Example 1 is that this example does not contain modified fibers.
[0046] Comparative Example 3: The difference from Example 1 is that an equal amount of basalt fiber is used instead of modified fiber in this example.
[0047] Performance testing: The PTFE composite tape material samples provided in Examples 1-3 and Comparative Examples 1-3 were labeled as Examples 1-3 and Comparative Examples 1-3, respectively; and the relevant properties of the PTFE composite tape materials provided in Examples 1-3 and Comparative Examples 1-3 were tested as follows: 1. Elongation test: The test shall be conducted in accordance with the testing standard of HG / T 3028-1999.
[0048] 2. Abrasion resistance test: The test shall be conducted in accordance with the test standard of GB / T5478-2008, and the wear amount (mg) at 1000r shall be calculated. Each group shall be tested 3 times and the average value shall be taken.
[0049] The obtained test data are recorded in Table 1 and Table 2 below.
[0050]
[0051]
[0052] By comparing and analyzing the relevant data in Tables 1 and 2, it can be seen that the low-elongation PTFE composite tape material prepared by this invention not only has a low elongation at break, but also excellent wear resistance, effectively ensuring its quality and performance. This indicates that the low-elongation PTFE composite tape material and its preparation process provided by this invention have a broader market prospect and are more suitable for widespread application.
[0053] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0054] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A low-elongation PTFE composite tape material, characterized in that, It is composed of the following raw materials in parts by weight: 20-30 parts polytetrafluoroethylene, 3-6 parts functional powder, 3-5 parts modified fiber, 2-4 parts nano titanium dioxide, 3-5 parts paraffin oil and 2-5 parts antioxidant. The preparation process of the functional powder is as follows: An appropriate amount of anhydrous ethanol, toluene, and hexadecyltrimethoxysilane were placed in a stirring device at a mass ratio of 1:0.6-0.8:0.12-0.22 and mixed for 20-30 minutes at 120-220 r / min. The pH value was then adjusted to 8.2-8.8 with sodium hydroxide solution to obtain the pre-mixed solution. Then, add 0.23-0.43% of the pre-mixed liquid as base material, and treat it at 8000-10000 r / min for 20-30 min, and then continue to treat it at 60-64℃ and 120-220 r / min for 300-320 min. After filtration, wash it 2-4 times with anhydrous ethanol and deionized water respectively. The washing product is dried at 50-60℃ for 10-12 h to obtain functional powder. The preparation process of the base material is as follows: A suitable amount of titanium source material is placed in a suitable amount of deionized water at a mass ratio of 0.12 to 0.22:1 and treated at 120 to 220 r / min for 20 to 30 min. Silica is then added, with the amount of silica added being 20 to 26% of the mass of the titanium source material. The pH value is adjusted to 7.0 to 7.4 with sodium hydroxide solution, and the mixture is treated at 55 to 65°C for 100 to 120 min. After cooling to room temperature, the mixture is filtered. The resulting filter cake is washed 2 to 4 times with deionized water and dried at 50 to 60°C for 4 to 5 h to obtain the dried product. The dried product was placed in an appropriate amount of deionized water and ultrasonically treated for 20-30 min at a solid-liquid ratio of 0.02-0.05 g / mL. Then, an appropriate amount of glacial acetic acid was added to adjust the pH value to 2.1-2.
5. The product was then dried at 50-60℃ for 4-5 h and calcined at 510-520℃ for 120-140 min to obtain the base material. The preparation process of the modified fiber is as follows: The nano-hollow glass microspheres were placed in a compound solution at a solid-liquid ratio of 0.02–0.12 g / mL for 24–26 h, filtered, and then treated at 120–130 °C for 100–120 min to obtain pretreated nano-hollow glass microspheres. Basalt fibers were ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.02–0.08 g / mL for 20–30 min. Then, 0.13–0.33% citric acid was added to the basalt fibers, and the mixture was treated at 120–140 r / min for 25–35 min. The temperature was then raised to 60–70 °C and kept at 140–150 min. The mixture was then treated at 5–10 °C and 120–140 r / min for 30–40 min. After filtration, the mixture was washed 2–4 times with deionized water and then dried at 50–60 °C for 10–12 h to obtain pretreated basalt fibers. Pretreated basalt fibers were ultrasonically dispersed in N,N-dimethylformamide at a solid-liquid ratio of 0.02–0.06 g / mL for 4–10 h. 1.4–6.4% of pretreated hollow glass nanospheres were added to the mixture, and the mixture was treated at 85–135 °C for 3–6 h. After filtration, the mixture was washed 2–4 times with deionized water and then dried at 50–60 °C for 10–12 h to obtain modified fibers.
2. The low-elongation PTFE composite tape material according to claim 1, characterized in that, The titanium source material is selected from either titanium nitrate or titanium sulfate.
3. The low-elongation PTFE composite tape material according to claim 1, characterized in that, The compound solution is prepared by mixing N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, ethanol and distilled water in a mass ratio of 1:8.8-9.2:1.2-1.
4.
4. The low-elongation PTFE composite tape material according to claim 1, characterized in that, The antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.
5. The preparation process of the low-elongation PTFE composite tape material according to any one of claims 1 to 4, characterized in that, Includes the following steps: Step 1: Accurately weigh polytetrafluoroethylene, functional powder, modified fiber, nano titanium dioxide, paraffin oil and antioxidant, and put them into the mixing equipment for mixing and stirring. Step 2: After the mixture is evenly mixed, the mixture is extruded into strips using a pusher at 60-150℃, and then rolled into thin sheets using a twin-roll calender at 92-100℃. The resulting thin sheets are then rolled at room temperature using a twin-roll calender to obtain a semi-finished PTFE composite belt. Step 3: Heat the obtained PTFE composite tape semi-finished product at 310-330℃ for 12-22 seconds to obtain low elongation PTFE composite tape material.
Citation Information
Patent Citations
PTFE composite tape for aerospace cables and its preparation method
CN111004462B
Preparation method of polytetrafluoroethylene ultra-thin filament
CN119332365A
